The XYU-GEM: Ambiguity-free coordinate readout of the Gas Electron Multiplier - Flöthner, K. J.; Janssens, D.; Brunbauer, F.; Ferry, S.; Ketzer, B.; Lisowska, M.; Muller, H.; de Oliveira, R.; Oliveri, E.; Orlandini, G.; Pfeiffer, D.; Samarati, J.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2023)
We describe the development of a position-sensitive Gas Electron Multiplier detector prototype, providing for each ionizing event three coordinates: the cartesian X and Y, and U at 45°. Simultaneous recording of the three projections permits ambiguity-free reconstruction of multiple tracks, and aims at operation in very high intensity radiation fields.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Gas Electron Multiplier (GEMs); Micropattern gaseous detectors; Position reconstruction; Spatial resolution